2015
DOI: 10.1589/jpts.29.2887
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an ankle foot orthosis on the percentage of weight loading during standing tasks in stroke patients

Abstract: [Purpose] The aim of this study was to investigate the effects of an ankle foot orthosis on weight-bearing abilities of stroke patients by comparing weight loading during performance of tasks in various standing positions on the affected side. [Subjects and Methods] This study was performed with 16 stroke patients. To measure the weight loading value and percentage of weight loading in affected lower extremities, 5 standing tasks were performed with and without an ankle foot orthosis in random order. [Results]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…22 We only found studies on AFO users with spastic ankle muscle paresis standing up from a chair. 23,24 Both studies found a better weight distribution with AFOs 23,24 but did not report participant’s ideas on the importance or difficulty of standing up from a chair, which is an opportunity for future research.…”
Section: Discussionmentioning
confidence: 94%
“…22 We only found studies on AFO users with spastic ankle muscle paresis standing up from a chair. 23,24 Both studies found a better weight distribution with AFOs 23,24 but did not report participant’s ideas on the importance or difficulty of standing up from a chair, which is an opportunity for future research.…”
Section: Discussionmentioning
confidence: 94%
“…Besides gait, it was hypothesized that balance would also be positively affected by wearing an AFO. Prior studies have reported that wearing an AFO provided mediolateral stability during stance 6 , 7 , 10 , 11 , 24 , 33 , 34 , 35 ) and corrected the ankle joint alignment 3 , 6 ) . These changes can positively influence the balance, which is confirmed by the data and results from the GAITRite ® .…”
Section: Discussionmentioning
confidence: 99%
“…The question wording and choices for the survey were informed by the BPS, 11 Bowers and Ross' paper on the development of the BPS, 9 papers regarding AFO use in post-stroke patients, 4,5,10,[12][13][14][15][22][23][24][25][26] discussion with experts and information from books, and papers regarding designing health care surveys. [17][18][19][20][21][27][28][29][30][31] The wording of the multiple-choice responses to five questions was taken directly from the Screening Tool associated with the BPS to assess participants' understanding and ability to use this Tool.…”
Section: Survey Designmentioning
confidence: 99%
“…Their use is supported for post‐stroke patients by SIGN Guideline 118, the International Society of Prosthetics and Orthotics (ISPO) Consensus Conference on Stroke, and the Best Practice Statement: Use of Ankle‐Foot Orthoses Following Stroke (BPS) . AFOs have been shown to improve walking speed, weight bearing asymmetry, stride length, patient self‐confidence, and completion of functional tests in post‐stroke patients.…”
Section: Introductionmentioning
confidence: 99%